Cooperation, Stability and Self-Enforcement in International Environmental Agreements: A Conceptual Discussion - Henry Tulkens; Parkash Chander (Fondazione Eni Enrico Mattei (FEEM), 2006)
In essence, any international environmental agreement (IEA) implies cooperation of a form or another. The paper seeks for logical foundations of this. It first deals with how the need for cooperation derives from the public good aspect of the externalities involved, as well as with where the source of cooperation lies in cooperative game theory. In either case, the quest for efficiency is claimed to be at the root of cooperation. Next, cooperation is considered from the point of view of stability. After recalling the two competing concepts of stability in use in the IEA literature, new insights on the nature of the gamma core in general are given as well as of the Chander-Tulkens solution within the gamma core. Free riding is also evaluated in relation with the alternative forms of stability under scrutiny. Finally, it is asked whether with the often mentioned virtue of self enforcement any conceptual gain is achieved, different from what is meant by efficiency and stability. A skeptical answer is offered, as a reply to Barretts (2003) attempt at giving the notion a specific content.
Keywords: C6; C7; C71; D62; H23; Q58; 330; International Environmental Agreements; Cooperation; Stability; Self-enforcement; Umweltabkommen; Kooperatives Spiel; Trittbrettfahrerverhalten; Externer Effekt; Selbstverpflichtung; Theorie